PENINGKATAN HASIL BELAJAR PKn PADA MATERI ANCAMAN TERHADAP INTEGRASI NASIONAL SISWA KELAS X IPS.5 SMAN 1 RAMBAH MELALUI METODE SNOW BALL THROWING T.P 2019/2020 - Elpita Nengsih (JURNAL PENDIDIKAN ROKANIA, 2020)
Civics learning that is closely related to daily events requires a good understanding by students, so that the knowledge gained can be practiced to solve life problems encountered by students in their lives. The teacher as a driving force for learning innovates so students are accustomed and interested in improving their learning outcomes. On this material threat to national integration, the teacher made an update with a study using the snow ball throwing method. The process is the teacher submits the subject matter in accordance with the learning plan, asking students to form pairs groups (two people) where the group is given the task to solve the five questions given by the teacher. Then one group joins another group, thus forming a new group of four people where the task is the same as the original group. The results of the group study are delivered in front of the class, then provide a review to clarify the group's learning. The results of the study can be concluded: 1) The learning outcomes of Civics students before applying the snow ball Throwing learning method in class X students of IPS.5 SMAN 1 Increased Even Semester Academic Year 2019/2020 with completeness of 52.94%. 2) Student learning outcomes in Civics material "threat to national integration" after applying the learning model of snow ball games in class X students of IPS.5 SMAN 1 Entering Even Semester 2019/2020 Academic Year obtained mastery learning as much as 82.36%, an increase in completeness which is significant on student learning outcomes.